2004
DOI: 10.1183/09031936.04.00039704
|View full text |Cite
|
Sign up to set email alerts
|

3-Min step test and treadmill exercise for evaluating exercise-induced asthma

Abstract: A simple exercise test would be useful for detecting exercise-induced asthma, a common problem in asthmatic children. The current study compared the 3-min step test with treadmill exercise for evaluating exercise-induced asthma in asthmatic children and assessed whether responses to both tests are influenced by baseline lung function and habitual physical activity.A series of 154 asthmatic children (84 male children; mean age 12.9 ¡ 0.9 yrs) underwent a 3-min step-test and treadmill testing on different days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
0
27
1
1
Order By: Relevance
“…25 The cadence changes during the Chester step test determine the increase in the work intensity, which precipitates the perceived exertion, leading patients to discontinue the test at a similar stage to that achieved in the previous test. Patients with cystic fibrosis 5 and exerciseinduced asthma 7 showed better reproducibility in a step test than we observed. Both of the latter studies used a 3-min step test, and though some of the children could continue the test, it was interrupted when the established end-time was reached, and we suspect that the short test duration probably contributed to the excellent reproducibility.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…25 The cadence changes during the Chester step test determine the increase in the work intensity, which precipitates the perceived exertion, leading patients to discontinue the test at a similar stage to that achieved in the previous test. Patients with cystic fibrosis 5 and exerciseinduced asthma 7 showed better reproducibility in a step test than we observed. Both of the latter studies used a 3-min step test, and though some of the children could continue the test, it was interrupted when the established end-time was reached, and we suspect that the short test duration probably contributed to the excellent reproducibility.…”
Section: Discussioncontrasting
confidence: 54%
“…The step test is widely used in healthy subjects, and several step test protocols have been adapted to study various outcomes in cardiopulmonary diseases. [3][4][5][6][7][8][9][10][11][12][13] The advantage of the step test over the 6-min walk test or shuttle test is that the step test requires less space and therefore can be conducted in settings such as an intensive care unit, a physician's office, or at a home-based or inpatient rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of the different step tests has been studied among patients with idiopathic pulmonary fibrosis 23 , COPD 16 , asthma 24 , or cystic fibrosis 25 . Although Swinburn et al 26 observed great variation between the four step tests conducted on patients with COPD, most studies have found the opposite (i.e., little variation between the step tests among patients with chronic lung disease 16,[23][24][25] ). In patients with COPD, the CST was highly reliable for tests conducted on the same day 16 , with an ICC of 0.99 (95% CIs=0.97 to 0.99) for NOSs.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this test was reliable with regard to the evaluation of SpO 2 , HR, dyspnea perception, and NOSs in 11 of 12 individuals. Tancredi et al 24 studied children with asthma by comparing two 3-min step tests conducted on a single 30-cm step at a pace of 30 steps/min across different days. These authors did not find differences in maximal HR (191±4.6 bpm and 192±5.0 bpm) or a drop in FEV 1 (12.8±5.9% and 12.1±5.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The 6MWT followed the standards of the ATS 20 . To ensure mouth breathing, a nose clip was used during the test, as recommended by other authors to check the occurrence of EIB [21][22][23] . The physical performance on the test was determined through the total walked distance (WD), in ms, and the maximal heart rate was obtained through the formula: HRmax=210-(0.65 x yrs of age) 5 .…”
Section: Six-minute Walking Testmentioning
confidence: 99%